Studies on Characterization, Optical Absorption, and Photoluminescence of Yttrium Doped ZnS Nanoparticles - Ranganaik Viswanath; Halehatty Seethya Bhojya Naik; Yashavanth Kumar Gubbihally Somalanaik; Prashanth Kumar Parlesed Neelanjeneallu; Khandugadahalli Nagarajappa Harish; Mustur Channabasappa Prabhakara (Journal of Nanotechnology)
Pure ZnS and ZnS:Y nanoparticles were synthesized by a chemical coprecipitation route using EDTA-ethylenediamine as a stabilizing agent. X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectrometry (FTIR), thermogravimetric-differential scanning calorimetry (TG-DSC), and UV-visible and photoluminescence (PL) spectroscopy were employed to characterize the as-synthesized ZnS and ZnS:Y nanoparticles, respectively. XRD and TEM studies show the formation of cubic ZnS:Y particles with an average size of ~4.5 nm. The doping did not alter the phase of the zinc sulphide, as a result the sample showed cubic zincblende structure. The UV-visible spectra of ZnS and ZnS:Y nanoparticles showed a band gap energy value, 3.85 eV and 3.73 eV, which corresponds to a semiconductor material. A luminescence characteristics such as strong and stable visible-light emissions in the orange region alone with the blue emission peaks were observed for doped ZnS nanoparticles at room temperature. The PL intensity of orange emission peak was found to be increased with an increase in yttrium ions concentration by suppressing blue emission peaks. These results strongly propose that yttrium doped zinc sulphide nanoparticles form a new class of luminescent material.